Pengaruh Kualitas Pelayanan dan Kepuasan Konsumen Terhadap Loyalitas Konsumen (Studi Kasus di Janji Jiwa 213 Gressmall Gresik) - NorNor Rahmat Syaikhuddin; Hamidah Hendrarini; Nuriah Yuliati (JURNAL PERTANIAN, 2025)
This study aims to determine the relationship between customer satisfaction and service quality at Janji Jiwa 213 Gressmall. This study uses a non-probability approach with a purposive sampling technique to select a sample of 100 respondents. Data were analyzed using the Structural Equation Model Partial Least Square (SEM PLS) method. The results showed a fairly large correlation between customer satisfaction and service quality on customer loyalty with a value of p <0.05.